Business Communication Strategy for Street Vendors in Gambir Tembung Market - Sari, Ria Novita; Ritonga, Muhammad Husni; Jailani, Muhammad (Pena Cendekia Insani, 2023)
The purpose of this study was to determine the business communication strategy used by street vendors at Gambir Tembung Market, Percut Sei Tuan District, Deli Serdang Regency in selling their wares. In this case, the authors use field research, which is a research that can retrieve the desired data that will be found directly in the field. This investigation obtains data directly from respondents through observation and interviews arranged according to the research objectives. This research uses (descriptive analysis research), namely research that describes and interprets what is there. The object of this research is street vendors in Gambir Tembung Market, Percut Sei Tuan District, Deli Serdang Regency. Regarding the results of the research that the author obtained from street vendors at Gambir Tembung Market, Percut Sei Tuan District, Deli Serdang Regency, regarding the types of merchandise, namely: Vegetable traders, chili traders and basic food traders.